Kidney transplantation and evolution of parathyroid function: results of a single-center study - O. N. Vetchinnikova (Трансплантология (Москва), 2025)
Background. The functional status of the parathyroid glands (PTG) in patients with chronic kidney disease (CKD) before and after kidney transplantation (KT) is interrelated. The preoperative optimal blood level of parathyroid hormone (PTH) for the prevention of the post-transplant hyperparathyroidism (HPT) development is unknown.The objective was to study the function of the PTG after KT during the first postoperative year depending on the pretransplant serum PTH level in the target range (150–600 pg/mL).Material and methods. The retrospective cohort single-center study included 157 patients with preoperative blood PTH levels of 150–600 pg/mL who had undergone primary successful KT for CKD G5-G5(D) at least a year before inclusion in the study. Serum concentrations of PTH, calcium, adjusted for albumin, phosphorus, and creatinine were studied before KT and at 3 and 12 months after it. Blood PTH no more than 130 pg/mL was a target level after KT.Results. Patients were allocated into three groups: 82 patients with blood PTH of 150–300 pg/mL were included into the 1st group; 41 patients with blood PTH of 301–450 pg/mL comprised the 2nd group, and 34 patients with blood PTH of 451–600 pg/mL made the 3rd group. Three months after KT, blood PTH decreased to 128 (98;169) pg/mL, 180 (121;222) pg/mL, and 247 (154;299) pg/mL (p<0.001) in the 1st, 2nd, and 3rd patient groups, respectively; the target blood PTH level was observed in 58.5%, 34.1%, and 20.6% of patients in the respective groups (p<0.001). No differences in the in PTG values were seen between the groups by the end of the year. A decrease in phosphorus and stable normal blood calcium were recorded. The graft function was similar in the patients of all groups throughout the year. A direct close correlation was established between blood PTH before KT and three months after KT, a less close one after one year; the relationship between blood PTH and graft function was weak after three months and a close one after one year.Conclusion. The process of normalization of PTG function in the early stages after successful KT depends on the preoperative blood PTH level.